THE METHOD OF OPTIMIZING THE DISTRIBUTION OF RADIO SUPPRESSION MEANS AND DESTRUCTIVE SOFTWARE INFLUENCE ON COMPUTER NETWORKS - Sholokhov, S. M.; Pavlenko, P. M.; Nikolaienko, B. A.; Samborsky, I. I.; Samborsky, E. I. (Radio Electronics, Computer Science, Control, 2023)
Context. Currently, generalized methodical approaches to the development of scenarios of complex radio suppression and electromagnetic influence of typical special telecommunication systems have been developed. However, during the development of possible cases for the complex application of radio suppression and destructive software influence,the problem of optimizing the resource of these means and its distribution according to the goals of radio suppression and objects of destructive computer influence arose, which has not yet been fully resolved.Especially in the literature known to the authors, there is no method for optimizing the resource distribution of radio and computer influence, used for the development and practical implementation of optimal scenarios of destructive influence on computer networks of enemy military groups in military operations. Therefore, it is necessary to formulate a problem and develop a method of optimizing the distribution of the resource of radio suppression and destructive software influence for the development of possible scenarios of the enemy’s violation of information exchange in a standart telecommunication network. Objective. The purpose of the research is to develop a method for optimizing the distribution of the resource of radio suppression and destructive software influence for the development of scenarios of information exchange violations by the enemy in the telecommunications network. Method.To achieve the purpose of the research, the methods of nonlinear optimization of heterogeneous resource distribution, mass service theory, and expert evaluation were comprehensively applied and developed in the field of modeling of information conflict. To determine the coefficients of protection of objects from radio-electronic and destructive computer influence, expert evaluation methods are used, in particular, the method of frequencies of preferences of the decision-maker using the Thurstone method. This method requires only one expert (a decision-maker), minimal communication time with him, minimal expert information (full ordering of weighting factors) and can be applied with a small number of evaluated weighting factors. To solve the problem of optimal distribution of a heterogeneous resource of means of destructive influence, to ensure the value of the multiplicative objective function of an arbitrary form is not less than the given one, the method of successive increments is applied. To determine the efficiency indicator of information exchange violation, the methods of mass service theory are applied, which allows to formalize special telecommunication systems as a set of mass service systems – subsystems of digital communication and computer networks. Results. The formulated problem and the entered indicators made it possible to solve the problem of determining the minimum resource of means of destructive influence and their optimal distribution according to the purposes of radio suppression on the objects of destructive program influence in order to achieve the required level of disruption of the efficiency of information exchange in special telecommunication systems. Conclusions.According to the results of the article, a method for optimizing the distribution of the resource of radio suppression and destructive software influence has been developed for the development of possible scenarios of information exchange violations by the enemy in a typical telecommunications network.The verification of the proposed method was carried out by comparing the theoretical results with the results of simulated modeling of scenarios of violation of the information exchange in the telecommunications network by the enemy.